Theory of diffusivelight scattering from disordered materials - WEAIRE, DENIS LAWRENCE; LUNNEY, JAMES GERARD; HUTZLER, STEFAN (International Society for Optical Engineering, 1994)
It is suggested that the measurement of the angular distribution of light transmitted through a thick slab of diffusively scattering material may provide information about the nature of the local scattering events. Monte Carlo simulations indicate that the angular distribution depends on eie* where and e* are the true and transport mean free paths, respectively, and this dependence is confirmed analytically using a modified diftusion model. Preliminary experimental results for liquid and solid foams are explicable in terms of strong forward scattering in the individual scattering events.
PUBLISHED
Keywords: Physics